IMPLEMENTASI ZAKAT PERBANDINGAN HISTORICAL COST DAN CURRENT VALUE - Chairul Iksan Burhanuddin; Muhammad Alfirga MS (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This research aims to look at comparison of calculation by using the method of historical cost and current value in the valuation of assets as a basis in determining the company's zakat. The methods used in this research was done by way of interpretation upon phenomenology in one of the private companies. The results showed that the calculation of the current value of generating bigger numbers were modest compared with the historical cost. In other words, the more alms distributed then the more companies/organizations that help people who are still poverty.